Factors Affecting Online Buying Behavior on G-Market Site among International Students in Busan: A Qualitative Research - Rianmahardhika Sahid Budiharseno (LifeSciFi, 2017)
Among the international students in South Korea, shopping activity is one of their favorites outside study. There are so many promotion periods which attract consumer purchasing intention, such as Black Friday, pepero day, year-end sale, etc. The purpose of this study was to explore the factors influencing the online buying behavior of the college students. Qualitative analysis was used for analyzing the data. Beside of offline purchase, online purchasing also have many interests among international students, especially on G-Market site, one of the biggest e-commerce sites in Korea. Based on their experiences, this study reveals that online shopping is cheaper than offline shopping. Moreover, it is also more efficiently for them because they have many class to attend.